"We have never been public:" Continuity and change in the policy production of "the public" in education in England. (January 2022) - Clarke, Matthew; Mills, Martin
Recent educational reforms in England have sought to reshape public education by extending central government control of curriculum and assessment, while replacing local government control of schools with a quasi-private system of academies and multi academy trusts. In this paper, we resist reading this as the latest iteration of the debate between "traditional" and "progressive" education. Instead, we note how, despite the mobilisation of the rhetoric of the public and public education, schooling in England has never been public in any deeply meaningful sense. We develop a genealogical reading of public education in England, in which ideas of British universalism – "the public" – and inequality and exclusion in education and society have not been opposed but have gone hand-in-hand. This raises the question whether it is possible to envisage and enact another form of collective – one that is based on action rather than fantasy and that is co-authored by, comprising, and exists for, the people. The final part of this paper seeks to grapple with this challenge, in the context of past, present and future potential developments in education, and to consider possibilities for the imaginary reconstitution of public education in England in the twenty-first century.